Upaya Meningkatkan Kemandirian Pengambilan Keputusan Karir Melalui Layanan Bimbingan Karir - Iik Damayanti; Yurike Kinanthy Karamoy; Wahyuni Wahyuni (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2021)
Independence of career decision making is independent attitude in making career decisions. Independent attitudes are confidence, responsibility, do not need helping to each other, turn and develop themselves, to be diligent, creative, initiative people. Classical career guidance service is career guidance service in the class. This research goal is to know the increase of students’ total that having the high independence level of career decision making. This research uses counseling guide action research as research type and questionnaire as research method. Data analyst use percentage formula. The research subject is XI TSM2 student of SMK Berdikari Jember with 11 students. The result of the research is 4 students (37%) in before cycle I, 5 students (46%) in after cycle I, 6 students (55%) in before cycle II and 8 students (73%) in after cycle II. This shows that students’ total that having high independence level of career decision making is increase.  Keywords: career decision making; career guidance.